ANALISIS HUKUM KEIMIGRASIAN TERHADAP DOKUMEN PERJALANAN, VISA, TANDA MASUK, DAN IZIN TINGGAL DALAM PENGENDALIAN ORANG ASING DI INDONESIA - Fabio Dwi Prawira (STKIP Subang, 2026)
This study aims to analyze the role and function of travel documents, visas, entry permits, and residence permits within the Indonesian immigration legal system. The increasing mobility of people across countries requires an effective control system to maintain state sovereignty and legal certainty. This research uses a normative legal method with statutory and conceptual approaches. The data consist of primary legal materials, including Law Number 6 of 2011 concerning Immigration, and secondary legal materials such as books, scientific journals, and official documents. The results show that travel documents, visas, entry permits, and residence permits form an integrated system in immigration control. Travel documents function as official identification for international travel, visas serve as initial entry permits to Indonesian territory, entry permits act as legal validation upon arrival, and residence permits provide the legal basis for foreigners staying in Indonesia. However, in practice, several issues are still found, including lack of public understanding, misuse of visas, violations of residence permits, and overlapping regulations. Therefore, strengthening regulations, improving supervision, and enhancing public legal literacy are necessary to improve the effectiveness of the immigration system in Indonesia in a comprehensive and sustainable manner.